2021
DOI: 10.1093/infdis/jiab622
|View full text |Cite
|
Sign up to set email alerts
|

Yearlong COVID-19 Infection Reveals Within-Host Evolution of SARS-CoV-2 in a Patient With B-Cell Depletion

Abstract: B-cell depleting therapies may lead to prolonged disease and viral shedding in individuals infected with SARS-CoV-2 and this viral persistence raises concern for viral evolution. We report on the sequencing of early and late samples from a 335-day infection in an immunocompromised patient. The virus accumulated a unique deletion in the amino-terminal domain of the spike protein, and complete deletion of ORF7b and ORF8, the first report of its kind in an immunocompromised patient. Overall, the unique viral muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 27 publications
1
56
0
Order By: Relevance
“…Moreover, a strong selection on SARS-CoV-2 has been reported after convalescent plasma therapy in immunosuppressed individuals, leading to the emergence of viral variants with reduced susceptibility to neutralizing antibodies [12,21,22,32]. Interestingly, the presence of mutations was more frequently observed in samples of days 143 and 207 compared to the earliest available one, and it led to the identification of multiple intra-host microevolution pathways considering the 7-month period of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a strong selection on SARS-CoV-2 has been reported after convalescent plasma therapy in immunosuppressed individuals, leading to the emergence of viral variants with reduced susceptibility to neutralizing antibodies [12,21,22,32]. Interestingly, the presence of mutations was more frequently observed in samples of days 143 and 207 compared to the earliest available one, and it led to the identification of multiple intra-host microevolution pathways considering the 7-month period of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to differ from the observations of Al Khatib et al who reported increased numbers of biallelic subconsensus variants (indicating AAF:RAF mixtures) in individuals classified as severe cases compared to individuals with mild cases [30] with comorbidities similar to the IM- patients studied here. It is also important to acknowledge that we were not able to study single patients over extended time series known to have extended for up to one year by other investigators [46]. Therefore, we did not have the opportunity to compare potential evolution of SARS-CoV-2 variants within individual IM+ and IM- patients over time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given reports that have suggested evolution of complexed populations of SARS-CoV-2 in immunocompromised people [44][45][46][47], we were interested to compare infections between IM+ and IM-individuals. While normalizing for overall complexity by comparing infections that occurred within time-similar cohorts, we did not observe increased numbers of iSNVs in IMpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major deletions and loss of function mutations in accessory proteins are not uncommon 29 . Such mutations have been documented in immunocompromised patients and are generally associated with milder symptoms 30 . The accessory protein mutations emerging in this case are specific to residues of functional domains, implying a more nuanced effect, rather than more general loss of function mutations.…”
Section: Mutations In Immunomodulatory Viral Proteins and Their Predi...mentioning
confidence: 99%